High tolerance to temperature and salinity change should enable scleractinian coral Platygyra acuta from marginal environments to persist under future climate change. - Apple Pui Yi Chui; Put Ang (PLoS ONE)
With projected changes in the marine environment under global climate change, the effects of single stressors on corals have been relatively well studied. However, more focus should be placed on the interactive effects of multiple stressors if their impacts upon corals are to be assessed more realistically. Elevation of sea surface temperature is projected under global climate change, and future increases in precipitation extremes related to the monsoon are also expected. Thus, the lowering of salinity could become a more common phenomenon and its impact on corals could be significant as extreme precipitation usually occurs during the coral spawning season. Here, we investigated the interactive effects of temperature [24, 27 (ambient), 30, 32°C] and salinity [33 psu (ambient), 30, 26, 22, 18, 14 psu] on larval settlement, post-settlement survival and early growth of the dominant coral Platygyra acuta from Hong Kong, a marginal environment for coral growth. The results indicate that elevated temperatures (+3°C and +5°C above ambient) did not have any significant effects on larval settlement success and post-settlement survival for up to 56 days of prolonged exposure. Such thermal tolerance was markedly higher than that reported in the literature for other coral species. Moreover, there was a positive effect of these elevated temperatures in reducing the negative effects of lowered salinity (26 psu) on settlement success. The enhanced settlement success brought about by elevated temperatures, together with the high post-settlement survival recorded up to 44 and 8 days of exposure under +3°C and +5°C ambient respectively, resulted in the overall positive effects of elevated temperatures on recruitment success. These results suggest that projected elevation in temperature over the next century should not pose any major problem for the recruitment success of P. acuta. The combined effects of higher temperatures and lowered salinity (26 psu) could even be beneficial. Therefore, corals that are currently present in marginal environments like Hong Kong, as exemplified by the dominant P. acuta, are likely to persist in a warmer and intermittently less saline, future ocean.